DIFFERENT APPROACHES TO THE DEFINITION OF THE CONTENT OF THE CONCEPT "ACTIVE COMMUNICATIVE POSITION" IN SCIENTIFIC RESEARCH - Shcherbyna, D.V. (Pedagogy of Higher and Secondary Education, 2022)
Various theoretical approaches to the definition of insight and the contents of the terms “active communicative position ” in scientific research are considered in the article. The author substantiated the necessity o f the form ation o f the pupils’ active communicative position in the process o f studying.